SYMBOLIC EPIC WRITING IN CLASSICAL LITERATURE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the epic genre as one of the most comprehensive and accomplished forms of classical literature. It explores the close relationship between epic poetry and folklore traditions, emphasizing the harmony between written literature and oral folk creativity. The study analyzes the literary heritage of prominent poets who illuminated the history of literature through epic writing and enriched literary traditions through their works. Particular attention is devoted to symbolism, allegorical imagery, and the development of symbolic epic traditions in  classical Uzbek literature.
Keywords: : epic, folklore, Khamsa, traditional motifs, Panj Ganj, Yusuf and Zulaykha, Gul and Navruz, Gulshan al-Asrar, Sayfulmulk, Husn-u Dil, symbolism, classical poetry, Adab al-Muluk.